The Effectiveness of Group Counseling in Improving Students’ Social Interaction: A Systematic Literature Review - Muhammad Aulia; Darimis (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2026)
Students’ social interaction is a fundamental aspect of social and academic development; however, many students experience difficulties in establishing effective interpersonal relationships in the school setting. Group counseling has been widely implemented to address this issue; however, empirical findings remain fragmented and have not been systematically synthesized. This study aims to review and synthesize empirical evidence regarding the effectiveness of group counseling in improving students’ social interaction. The study employed a Systematic Literature Review (SLR) design based on the PRISMA framework. Literature searches were conducted using Google Scholar with the keywords “group counseling” and “student social interaction”, focusing on articles published between 2014 and 2024. Following a rigorous screening process, five eligible studies were selected for analysis. The findings indicate that group counseling consistently improves students’ social interaction through various approaches, including role playing, modeling, and Rational Emotive Behavior Therapy (REBT). Group dynamics play a central role in facilitating behavioral and cognitive change. In conclusion, group counseling is an effective and adaptable intervention for enhancing students’ social interaction, providing important implications for school counselors in designing evidence-based counseling programs.